Natural palettes : inspiration from plant-based color - Duerr, Sasha (New York : Princeton Architectural Press, 2020)
"An innovative plant-based color guide that includes twenty-five palettes with five hundred natural color swatches, providing inspiration for sustainable fashion, textiles, fine art, floral design, food, medicine, gardening, interior design, and other creative disciplines"--
Index, bibl.
Includes bibliographical references.
Keywords: Color in design; Dye plants